La historia detrás de las cifras: la evolución del censo chileno y la representación del trabajo femenino, 1895-1930 - Hutchison, Elizabeth Quay (Historia, 2000)
Historians have regularly assumed the transparency of census statistics on women's employment in Chile, which suggest a steady decline in female employment -particulary in industry- from the late nineteenth through the early twentieth century. Arguing that quantitative sources are like other historical documents social constructions, this article first explores the limitations of the Chilean census as an accurate measure of female economic activity. The article hen shows how, because the progressive "modernization" of the census implied